2011
DOI: 10.1073/pnas.1116162108
|View full text |Cite
|
Sign up to set email alerts
|

Malaria antifolate resistance with contrasting Plasmodium falciparum dihydrofolate reductase (DHFR) polymorphisms in humans and Anopheles mosquitoes

Abstract: Surveillance for drug-resistant parasites in human blood is a major effort in malaria control. Here we report contrasting antifolate resistance polymorphisms in Plasmodium falciparum when parasites in human blood were compared with parasites in Anopheles vector mosquitoes from sleeping huts in rural Zambia. DNA encoding P. falciparum dihydrofolate reductase (EC 1.5.1.3) was amplified by PCR with allele-specific restriction enzyme digestions. Markedly prevalent pyrimethamine-resistant mutants were evident in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 40 publications
6
53
0
Order By: Relevance
“…Structural models of the pjDHFR ternary complex with OAAG324 show weaker interactions of the 5=-Cl of OAAG324 with Ser69. Similar observations were made that helped explain the gain of function observed for the S108T mutation in Plasmodium falciparum DHFR (29).…”
Section: Figsupporting
confidence: 61%
See 1 more Smart Citation
“…Structural models of the pjDHFR ternary complex with OAAG324 show weaker interactions of the 5=-Cl of OAAG324 with Ser69. Similar observations were made that helped explain the gain of function observed for the S108T mutation in Plasmodium falciparum DHFR (29).…”
Section: Figsupporting
confidence: 61%
“…The K i values for OAAG324 were determined for all native and mutant DHFR forms from pj-, pc-, and hDHFR. Substitution of amino acids from the pjDHFR sequence into the active site of hDHFR lowered the K i , i.e., improved the binding of OAAG324 (and thus, resulted in gain of function [29]) (Table 3 and Fig. 6a); the Q35S/N64S double variant shows a K i value of 2.47 Ϯ 0.5 nM (mean Ϯ standard deviation), which is statistically significantly lower than the value for hDHFR (24.3 Ϯ 4.4 nM) and is similar to that for pjDHFR (2.7 Ϯ 0.4 nM).…”
Section: Figmentioning
confidence: 99%
“…In the context of the natural conditions of transmission in Burkina, the interaction between P. falciparum field isolates with the local mosquito populations could have favored selection of this particular var gene if there is a survival advantage to the mosquito by conferring or increasing resistance to disease. Other types of selection events related to pleiotropy or gene linkage of the selected variant to certain drug-resistance alleles cannot be ruled out63.…”
Section: Discussionmentioning
confidence: 99%
“…Differences have also been found in drug-resistant associated genes. In Gabon, Mharakurwa et al [5] reported that parasites in humans presented high levels of pyrimethamine (PYR)-resistant mutants, whereas parasites in Anopheles mosquitoes showed high levels of cycloguanil-resistant mutants.…”
Section: Introductionmentioning
confidence: 99%